2003
DOI: 10.2343/geochemj.37.671
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rare-earth elements in rock samples by an improved high-performance ion chromatography

Abstract: An analytical technique of rare-earth elements (REE) in rock samples using a high-performance ion chromatography (HPIC) is described. The REE in rock samples were separated from other elements using a conventional ion-exchange column, and then measured by the HPIC. α-hydroxyisobutyric acid and Arsenazo III were used for eluants and a post-column reagent for the HPIC, respectively. The use of a high-resolution HPIC column enabled to analyze all fourteen REE without any interference from Y and other transition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The associated analytical methods are currently under development. It must be noted that because of the numerous Ln industrial applications, the separation of the series of lanthanide ions has been reported with other separation techniques such as ionic chromatography, 41 ion pairing reversed-phase chromatography, 42 capillary electrophoresis 43 and isotachophoresis. 44 All these techniques require the addition of ion pairing and/or complexing agents in the mobile phases for Ln elution and the use of complexing agents as constituents of background electrolyte to insure differential Ln migration.…”
Section: Resultsmentioning
confidence: 99%
“…The associated analytical methods are currently under development. It must be noted that because of the numerous Ln industrial applications, the separation of the series of lanthanide ions has been reported with other separation techniques such as ionic chromatography, 41 ion pairing reversed-phase chromatography, 42 capillary electrophoresis 43 and isotachophoresis. 44 All these techniques require the addition of ion pairing and/or complexing agents in the mobile phases for Ln elution and the use of complexing agents as constituents of background electrolyte to insure differential Ln migration.…”
Section: Resultsmentioning
confidence: 99%
“…Another method of sample ionisation, except for ICP that is commonly used for the REEs analyses, is thermal ionisation, in particular, isotope dilution-thermal ionisation mass spectrometry (ID-TIMS). Details about the advantages and disadvantages of these techniques can be found elsewhere (e.g., Ishikawa et al 2003). Briefly, ICP-MS is the method of choice for quantification of REEs if: (a) a precise quantification of all the REEs including the mono-isotopic elements (Pr, Tb, Ho and Tm) is required, (b) the expected mass fractions of REEs in samples are at the level of 1 µg g -1 and below, (c) samples are unique and limited quantities of material are available for analyses, and (d) nuclear reactor facilities are not accessible (nowadays INAA has been practically replaced by ICP-MS due to its complexity and associated costs).…”
Section: Overview Of Icp-ms Methods For Ree Quantification In Geological Samplesmentioning
confidence: 99%
“…Traditionally, during HPLC separations using HIBA (as the mobile phase), it has been found that Y co-elutes with Dy (e.g., Cassidy 1988;Verma 1991a, b, Na et al 1995, Santoyo and Verma 2003, Raut et al 2004, or less commonly with Ho (Watkins et al 1995, Inoue et al 1996. Probably in one study only (Ishikawa et al 2003; see Table 1), Y was completely separated from all lanthanides (Lu-La) with a 5 μm column maintained at 40 °C, the conventional mobile phase HIBA (but with a high concentration of 1.0 mol l -1 ), and a UV-Vis detection system. A different way to overcome this problem has been the use of an ICP-MS or ICP-AES detection system.…”
Section: Yttrium Co-elution Problemmentioning
confidence: 99%
“…Among the use of HPLC and HPIC for determination of the REEs, geological applications have represented an important research area (e.g., Cassidy 1988, Stray and Dahlgren 1995, Watkins et al 1995, Verma et al 2002, Ishikawa et al 2003, Santoyo et al 2006. Geological samples are generally characterised by complex mineralogical matrices.…”
mentioning
confidence: 99%